Meningkatkan Employe Performance Dengan Extrinsic Motivation Dan Interpersonal Trust Melalui Organizational Commitment - Didit Haryadi (eCo-Buss, 2022)
This study aims to examine and analyze the effect of extrinsic motivation and interpersonal trust on employee performance through organizational commitment. This study uses a descriptive quantitative method with a causal approach. The object of research on employees of PT. Nikomas Gemilang Serang Nike Ruuber Chemical Division used a sample of 120 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Extrinsic motivation has a significant effect on employee performance. 2). Interpersonal trust has a significant effect on employee performance. 3). Extrinsic motivation has a significant effect on organizational commitment. 4). Interpersonal trust has a significant effect on organizational commitment. 5). Organizational commitment has a significant effect on employee performance. Organizational commitment can mediate between extrinsic motivation and interpersonal trust with partial mediation.